1970
DOI: 10.1002/macp.1970.021350108
|View full text |Cite
|
Sign up to set email alerts
|

Attempted copolymerization of 1.3‐dioxolane with tetrahydrofuran by triethyl oxonium tetrafluoroborate

Abstract: Copolymerization of 1,3-dioxolane (DOL) with tetrahydrofuran (THF) was attempted with triethyl oxonium tetrafluoroborat+ (Et30BF4) as initiator. The gas chromatographic determination of the unreacted monomers during the reaction indicated that preferential polymerization of THF occurred in the initial stage of the reaction, and that once DOL began to polymerize after an induction period, the polymerization of T H F declined gradually and ceased. However, it was resumed, although very slowly, after the polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…3 studied the same copolymerization with Et 3 0SbCI 6 as an initiator and they concluded that the propagating species of DOL, which are supposedly solvated by THF monomers, grow only by the addition of DOL monomers, in agreement with the results of Yamashita et a/. 2 It seems strange at first glance that DOL cannot copolymerize with THF, because both DOL 4 · 5 and THF 6 • 7 copolymerize with 3,3-bischloromethyloxacyclobutane (BCMO), and both growing species of DOL and THF grow essentially by the SN2 mechanism, although the former has an oxycarbenium ionic character 8 -11 and the latter is a tertiary oxonium ionY One of the possible reasons for the reluctant cross-over propagations in the DOL-THF copolymerization system is the preferential occurrence of an oxonium ion exchange reaction at the growing chain end with DOL and THF units as the penultimate and terminal units, respectively. 2 Therefore, it would be expected that if the copolymerization is carried out under the conditions where propagations proceed through ester species, instead of ionic species, by using a superacid derivative as an initiator, a random copolymer might be formed from DOL and THF.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…3 studied the same copolymerization with Et 3 0SbCI 6 as an initiator and they concluded that the propagating species of DOL, which are supposedly solvated by THF monomers, grow only by the addition of DOL monomers, in agreement with the results of Yamashita et a/. 2 It seems strange at first glance that DOL cannot copolymerize with THF, because both DOL 4 · 5 and THF 6 • 7 copolymerize with 3,3-bischloromethyloxacyclobutane (BCMO), and both growing species of DOL and THF grow essentially by the SN2 mechanism, although the former has an oxycarbenium ionic character 8 -11 and the latter is a tertiary oxonium ionY One of the possible reasons for the reluctant cross-over propagations in the DOL-THF copolymerization system is the preferential occurrence of an oxonium ion exchange reaction at the growing chain end with DOL and THF units as the penultimate and terminal units, respectively. 2 Therefore, it would be expected that if the copolymerization is carried out under the conditions where propagations proceed through ester species, instead of ionic species, by using a superacid derivative as an initiator, a random copolymer might be formed from DOL and THF.…”
supporting
confidence: 65%
“…3 studied the same copolymerization with Et 3 0SbCI 6 as an initiator and they concluded that the propagating species of DOL, which are supposedly solvated by THF monomers, grow only by the addition of DOL monomers, in agreement with the results of Yamashita et a/. 2 It seems strange at first glance that DOL cannot copolymerize with THF, because both DOL 4 · 5 and THF 6 • 7 copolymerize with 3,3-bischloromethyloxacyclobutane (BCMO), and both growing species of DOL and THF grow essentially by the SN2 mechanism, although the former has an oxycarbenium ionic character 8 -11 and the latter is a tertiary oxonium ionY One of the possible reasons for the reluctant cross-over propagations in the DOL-THF 629 …”
supporting
confidence: 64%
See 2 more Smart Citations
“…According to this study, the variation in the exchange current obtained by electrochemical methods is due to modifications of the structural state of the deposit. Chiba et al [34] and Yamashita et al [35] found that a magnetic field had no effect on the rate-determining step in copper deposition, but did increase the charge-transfer current and the efficiency of the deposition process. In contrast, the ratedetermining step of p-benzoquinone reduction in acetonitrile shifts from mass to electron transfer when a strong magnetic field is applied [36].…”
Section: Kinetic Effectsmentioning
confidence: 99%